Heat transfer analysis in thermal entrance region under turbulent flow conditions. Issue 4 (22nd November 2012) - Hasan, Basim O.
ABSTRACT: Turbulent heat transfer in the thermal entrance region of the pipe was studied by numerical solution of the energy equation using finite difference technique under different operating conditions. The turbulence effect was accounted for by introducing thermal eddy diffusivity term in the energy equation in both axial and radial directions. The axial and radial temperature profiles, the local heat transfer coefficient in the entrance and fully developed regions, and the entrance lengths were obtained and discussed. In addition, the role of thermal eddy diffusivity in the thermal entrance region and fully developed region was investigated. The finite difference numerical solution was also commented on. The theoretical results were compared with previous experimental works, and a reasonably good agreement was found. It was found that the temperature gradient in axial direction is very steep, close to the leading edge near the pipe's surface and becomes almost negligible after a distance equals few pipe diameters, depending on Reynolds number ( Re ), Prandtl number ( Pr ), and heat flux ( q ). The radial temperature profile was very steep, close to the pipe's surface near the leading edge and becomes almost constant at a very short distance from the pipe surface, depending on Re, Pr, and q . The entrance length ( L t ) was found to be reached after 0.5–3.5 pipe diameters distance for the investigated ranges of Re, Pr, and q . Thermal eddy diffusivity plays an important role in axial and radial transport. Ignoring it, causes underestimation in the heat transfer coefficient and overestimation in the entrance length. © 2012 Curtin University of Technology and John Wiley & Sons, Ltd.